Prototyping the Design and Development of a School Feeding Project - R. TORRES, BEULAH ROSE (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This study describes the prototyping process of designing a university feeding project that exists in combination with the literacy project named Sa Karunumgan Walang Iwanan (SKaWI) spearheaded by the Social Sciences Department of Bukidnon State University, Philippines, during school year 2006-2007 until 2008-2009. It was to establish the current status and achievements of the program; and, to identify the series of actions taken that led to results. The United Nations checkist to design and update a new school feeding program was used to analyze the feeding project. Although the tool suggests a step-by step, sequential process, this study showed that in reality, the design and development stages may overlap, and may start with mere objectives. It further showed that what occurred in the design of the feeding project was consistent with the principles of a rapid prototyping design model in which project implementation may be started in its prototype form. Overall, the study indicates that this design strategy fosters shared understanding among its project designers, stakeholders and direct project participants.